Analisis Kelayakan Bisnis pada UMKM Banana Nugget di Bandung Timur - Rizal Maulana; Nopiyanti Rahmawati; Dinda Thalia Trianita (CARONG: Jurnal Pendidikan, Sosial dan Humaniora, 2025)
This research aims to analyze the business feasibility of Banana Nugget micro, small and medium enterprises (MSMEs) in the East Bandung area. The Banana Nugget business is a business that offers innovative food products made from bananas with a variety of flavors. The method used in this research is feasibility analysis which includes market study, technical analysis, financial analysis and managerial analysis. The research results show that the market for this product has good potential, with quite high demand, especially among young people and families. From a technical perspective, this business has a strategic location and an efficient production process